Topofilia, Turismo e a Releitura do Lugar: uma abordagem sociocultural do patrimônio histórico, arquitetônico e urbanístico de Diamantina/MG - Rahyan de Carvalho Alves (2014)
Landscapes allude to the existence and experience essence of a community space, being perceived with intensity and clearness in historical heritages, creators of live cultural and socio-political foundations. In this representative context of cultural links, many municipalities in Brazil, like Diamantina, Minas Gerais, present themselves as centers of material-holders elements under government trust, linked to architectural heritage sets (urban or rural), showing environments which lead to topophilia ties, important in perpetuating the collective life and psychosocial stability of the subject. Contemporaneously many elements under government trust are considered co-modified products, since the municipal public power and capitalist agents see them as potential for profitability. The performance of cultural tourism can interfere with its dynamic, in the sense of a life expressed in landscapes and cultural manifestations. This work aims to understand the positive and negative impacts that the activity of cultural tourism generates, through exposure of the architectural and urban heritage of Diamantina, Minas Gerais, affecting residents, interfering and eventually creating conflicts with their bonds of affection and sense of belonging to the place. As methodology it was used: bibliographical research, etnomethodologies supported in iconographic records, in addition to the Organization and systematization of data for preparing maps and graphs. While developing this work it could be noticed that for the diamantinense the representation of landscapes meaning offers a relationship of belonging, affectivity and memory deliverance that strengthens the relationships between resident and his place and his close ones. Soon the interference of tourist represents, there, the pursuit of experience through social contacts, provoking nuances of social tensions, but also enabling a similarity among tourists with local residents, since this activity is exerted, and perceived, beyond the goal of a market survival which develops through the consumption of tourists in this territorial clipping, achieving the outsider aggregate knowledge about historical aspects of this geographical place, acknowledging the importance of local residents and enabling the creation of friendship bonds. The interference of the cultural tourism dynamics in Diamantina, Minas Gerais, can't materialize in the resident a sense that refers to topophobia; besides the municipal public power realizes the importance of heritage to design the tourism in the city, managing to promote economic dynamics and, to some extent, providing socio-cultural junctions between the outsider and insider.